Assessment of knowledge, practice and associated factors towards prevention of novel corona virus among clients attending at Debre Tabor General Hospital, Debre Tabor Town, North West Ethiopia, 2020: Institutional based cross-sectional study - Emiru, Tigabu Desie; Birlie, Tekalign Amera; Tasew, Sheganew Fetene; Amare, Abraham Tsedalu; Tibebu, Nigusie Selomon; Tiruneh, Chalie Marew (Journal of Community Medicine and Health Solutions, 2020)
Background: Corona virus disease is a highly infectious disease caused by the newly innovated corona virus. An emerging respiratory disease was abbreviated as COVID-19, after it has been first reported in December 2019 in Wuhan city of China. Ethiopia Ministry of health initiated multidisciplinary approach to tackle COVID-19 of which awareness creation is the main. The aim of this study is to assess knowledge, practice and associated factors towards prevention of novel corona virus among clients in Debre Tabor general hospital, Northwest Ethiopia, 2020. Methods: Institution based cross sectional study design was conducted in Debre Tabor General hospital from May 15 to May 30, 2020. A structured questionnaire was used for data collection. The data were entered into epi data version 4.4 and exported to SPSS window version 25 for analysis. Binary and multivariable logistic regression was fitted. Odds Ratios with 95% Confidence interval and p - value ≤ 0.05 were considered to assert significance. Result: A total of 345 clients were analyzed and the response rate was 96.4%. The mean age was 32.95 with S.D ± 13.18 years. Majority of the respondents were male (75.7%). Among the study participants 54.2% with (95% CI: [49.0, 59.2%]) and 49.0% with (95% CI: [43.5, 53.4%]) have good knowledge and god practice on COVID-19 preventions respectively. Sex AOR: 4.33 (2.06, 9.09), family size AOR: 2.49 (1.01, 6.15 and heard from social media AOR: 2.78 (1.21, 6.39) were significantly associated with knowledge of respondents. Knowledge AOR: 3.11 (1.59, 6.10) was significantly associated with practice of clients. Residency and those heard from TV were significant variables for both. Conclusion and recommendation: In this study the overall knowledge and preventive practices of the respondents were found to be low. Sex, family size, residency and sources of information were associated factors for knowledge. In addition to this knowledge was significant factor for practice. Health education programs aimed at mobilizing and improving COVID-19 related knowledge and practice intend to be strengthened.